The Illusion of Suffrage: Female Voting Rights and the Women’s Poll Tax Repeal Movement After the Nineteenth Amendment - Podolefsky, Ronnie L. (Columbia Journal of Gender and Law, 1998)
A century of struggle preceded the 1920 passage of the Nineteenth Amendment, granting women the right to vote. Conventional wisdom holds that passage of the amendment heralded women’s right to vote and that, at the same time, it signaled the end of the women’s rights movement until the 1960s. This essay challenges both assumptions. The Southern poll tax, a charge of one or two dollars required for registering to vote,’ resulted in the disproportionate disfranchisement of millions of women. Evidence shows that women were actively fighting the effects of the poll tax by 1922. Organized repeal efforts were well underway by the 1930s and remained so until the poll tax was finally put to rest by constitutional amendment in 1964 and by the U.S. Supreme Court in 1966. The women’s movement to repeal the tax was in fact a manifestation of the women’s rights movement during an era generally hostile to feminists. Additionally, this movement evidenced women working together across racial lines, contradicting another widespread assumption about the women’s movement. The women’s rights movement didn’t end after suffrage. Instead, it survived, shaped by the relative friendliness and hostility of the political, social, and economic environment of the mid-twentieth century. Poll tax repeal through the political process was difficult since the tax disfranchised the very women who would vote for repeal. The Court remained unavailable to them for decades after a 1937 decision finding the tax constitutional. The movement directed its energies into whatever channels remained. Not readily recognized in the traditional form we have come to expect, the women’s rights movement was necessarily submerged within the identities of seemingly unrelated groups and individuals whose resources and power the women accessed.